Financial distress analysis using modified altman z-score model on PT.PLN (Persero) during the Covid-19 pandemic - Khanti Listya; Sri Liniarti; Rizki Surya Andhayani Nasution (Institute of Computer Science (IOCS), 2023)
During the Covid 19 Pandemic, many companies experienced financial problems and had the potential to go bankrupt. Companies feel this private and state-owned condition, one of which is PT. PLN. As a form of anticipation of bankruptcy, a system is needed that can provide an early warning—financial distress analysis at PT. PLN during the Covid-19 Pandemic can be done by analyzing the Modified Z-Score Model. From the calculation of Z-Score in 2019, it is 3,688. Where Z > 2.60 indicates that PT PLN's financial condition is in the safe zone. Where, PT. PLN in 2019 is in good health and has a tiny possibility of bankruptcy. In 2020, the calculation of Z-Score 2020 was more than 2.60, which is 3.4971. So in 2020, the financial condition of PT. PLN is also in the safe zone and less likely to go bankrupt. Meanwhile, based on the results of the Z-Score calculation in 2021, PT. PLN is 1.6727, where the Z-Score is 1.10 < Z < 2.6. Based on these values, PT. PLN is in a gray zone, where the company is vulnerable. In this condition, the company experiences financial problems that must be handled appropriately